Famílias de crianças autistas : compreendendo a participação e os desafios por meio do olhar paterno - Souza, Aline Cristina de (2016)
The changes that occurred with the paternal role over the years have a more involved parent affectively participating, whenever possible, everything that goes around your child.Such changes in parenting are changes reflections that occur among the family. Going through a metamorphosis, with currently new family rearrangements, the family also changed the configuration of their member. The same occurs when there is the presence of a disabled child in the family environment, new modifications tend to be carried out, thus aiming at the welfare of the child. Even with the later discovery, the same occurs with the disorder Autistic Spectrum - TEA. This is characterized by intellectual, communicative and social commitment, it has its later diagnosis, and its main features presented around 18 months old. The first investigations arise from observations of parents and close family members who notice a break in typical development that the child had been presenting and becomes no longer present. From this, the present study aims to: (a) to characterize and understand the parental relationship between parents and children with autism and (b) identify the father of the needs of children with autism. The participants were 15 parents (man), who had a son with autism. Data collection occurred with parents in a mediumsized municipality in the state of São Paulo. interviews with participants were carried out in addition to the use of Economic Classification Criteria Brazil - CCEB in order to characterize the family of the interviewed participants finally used the Needs Questionnaire Family - QNF. The data were analyzed qualitatively, performing content analysis. The results showed a greater participation of the father during pregnancy, and most of them said to have accompanied his wife in prenatal consultations. It was possible to verify that the diagnosis of autism prevailed around two years of age, however, the aspects that led parents to suspect this deficiency varied, highlighting the speech delay, followed by developmental delays, and behavioral changes. Parents held a self-analysis regarding the exercise of paternity and most of them said they consider a good father, however, others indicated that they could improve. Parents also showed their expectations about the future of the children, most parents pointed out that expects the child to be independent, followed by parents who expect the child to have a normal life. The results indicated QNF needs of parents regarding how to teach the child and the need for information regarding disability. From this, it follows that today men have a prominent role with the responsibilities to the child, even on domestic issues. The fact of having a child with autism brings challenges and needs, but many parents have managed to adapt the same.